Developments in the Tools and Methodologies of Synthetic Biology - Kelwick, Richard; MacDonald, James T.; Webb, Alexander J.; Freemont, Paul (Frontiers in Bioengineering and Biotechnology, 2014)
Synthetic biology is principally concerned with the rational design and engineering of biologically based parts, devices or systems. However, biological systems are generally complex and unpredictable and are therefore intrinsically difficult to engineer. In order to address these fundamental challenges, synthetic biology is aiming to unify a ‘body of knowledge’ from several foundational scientific fields, within the context of a set of engineering principles. This shift in perspective is enabling synthetic biologists to address complexity, such that robust biological systems can be designed, assembled and tested as part of a biological design cycle. The design cycle takes a forward-design approach in which a biological system is specified, modeled, analyzed, assembled and its functionality tested. At each stage of the design cycle an expanding repertoire of tools is being developed. In this review we highlight several of these tools in terms of their applications and benefits to the synthetic biology community.